2017
DOI: 10.1111/ajps.12314
|View full text |Cite
|
Sign up to set email alerts
|

A Bottom‐Up Theory of Public Opinion about Foreign Policy

Abstract: If public opinion about foreign policy is such an elite-driven process, why does the public often disagree with what elites have to say? We argue here that elite cue-taking models in International Relations are both overly pessimistic and unnecessarily restrictive. Members of the public may lack information about the world around them, but they do not lack principles, and information need not only cascade from the top down. We present the results from five survey experiments where we show that cues from social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
100
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(130 citation statements)
references
References 90 publications
12
100
2
Order By: Relevance
“…We believe that it is more likely that particular frames work better with some people given their preexisting moral foundations. The public is not as malleable as many assume (Kertzer & Zeitzoff, ). The Bild Zeitung , given the moral concerns of its readers, could not have articulated a probailout campaign that stressed the economic harm that austerity caused for Greek pensioners and widowers because it would not have resonated with its populist audience.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that it is more likely that particular frames work better with some people given their preexisting moral foundations. The public is not as malleable as many assume (Kertzer & Zeitzoff, ). The Bild Zeitung , given the moral concerns of its readers, could not have articulated a probailout campaign that stressed the economic harm that austerity caused for Greek pensioners and widowers because it would not have resonated with its populist audience.…”
Section: Resultsmentioning
confidence: 99%
“…Our two survey experiments in China provide suggestive evidence of authoritarian audience costs and indicate that some government explanations can be effective in justifying inaction. However, researchers have also shown that democratic governments are able to control the domestic costs of inaction or backing down through elite cues, 49 while others have highlighted the importance of social peers (Kertzer and Zeitzoff, 2017). Further research may wish to explicitly compare the extent to which democratic and authoritarian governments can shape domestic reactions to crisis developments-as well as how these mass incentives are communicated and understood by foreign decision-makers.…”
Section: Discussionmentioning
confidence: 99%
“…When juxtaposed with the large body of evidence showing that residents of strong states emphasize particularistic identities that encourage isolationist and xenophobic tendencies in response to acute threats (e.g., Feinstein 2016a), this presents an ironic dilemma: the reactions of residents of the same core states that largely constructed and continue to dominate the global order compose the greatest risk to its preservation. This circumstance suggests that individuals on the global periphery are less of a danger to the global order than residents of the global core; the latter are more likely to retreat to particularism under threat and have the power to alter their countries' foreign policies and relationships with the outside world (Kertzer and Zeitzoff 2017). Consider, for example, that residents of the United Kingdom, one of the world's most powerful countries, recently voted to leave the European Union, while residents of less powerful countries like Albania, Macedonia, Montenegro, and Serbia remain eager to join.…”
Section: Threat and The Future Of Global Identificationmentioning
confidence: 99%